The Effects of Adversity Quotient And Spiritual Quotient on Teacher Performance - muztaba, muztaba; Bahri, Syamsul; Farizal, Farizal (Universitas Syiah Kuala, 2020)
This study aims to examine and find out empirical data about the effect of adversity quotient and spiritual quotient on the performance of Al-Azhar Elementary School teachers, Depok City separately or simultaneously. In this study, the authors used a survey method with a correlational approach to quantitative data obtained from the research object. The type of analysis used is correlation and regression analysis which is described descriptively. The results of this study are: First, there is a positive and significant influence between adversity quotient and spiritual quotient of teachers in SD Al-Azhar 46 Depok City. Secondly, there is a positive and significant influence between spiritual quotient and teacher performance of Sd Al-Azhar 46 Depok City. There is a significant positive between Adversity Quotient and Spiritual Quotient. Fourth, there is a positive and significant influence between adversity quotient and spiritual quotient together (simultaneously) with the performance of teachers at SD Al-Azhar 46 Depok City.Keywords: Adversity quotient, spiritual quotient, teacher performance